Altered Mitochondrial Dynamics in Motor Neuron Disease: An Emerging Perspective - Manohar Kodavati; Haibo Wang; Muralidhar L. Hegde (Cells, 2020)
Mitochondria plays privotal role in diverse pathways that regulate cellular function and survival, and have emerged as a prime focus in aging and age-associated motor neuron diseases (MNDs), such as amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). Accumulating evidence suggests that many amyloidogenic proteins, including MND-associated RNA/DNA-binding proteins fused in sarcoma (FUS) and TAR DNA binding protein (TDP)-43, are strongly linked to mitochondrial dysfunction. Animal model and patient studies have highlighted changes in mitochondrial structure, plasticity, replication/copy number, mitochondrial DNA instability, and altered membrane potential in several subsets of MNDs, and these observations are consistent with the evidence of increased excitotoxicity, induction of reactive oxygen species, and activation of intrinsic apoptotic pathways. Studies in MND rodent models also indicate that mitochondrial abnormalities begin prior to the clinical and pathological onset of the disease, suggesting a causal role of mitochondrial dysfunction. Our recent studies, which demonstrated the involvement of specific defects in DNA break-ligation mediated by DNA ligase 3 (LIG3) in FUS-associated ALS, raised a key question of its potential implication in mitochondrial DNA transactions because LIG3 is essential for both mitochondrial DNA replication and repair. This question, as well as how wild-type and mutant MND-associated factors affect mitochondria, remain to be elucidated. These new investigation avenues into the mechanistic role of mitochondrial dysfunction in MNDs are critical to identify therapeutic targets to alleviate mitochondrial toxicity and its consequences. In this article, we critically review recent advances in our understanding of mitochondrial dysfunction in diverse subgroups of MNDs and discuss challenges and future directions.